2010
DOI: 10.1159/000285182
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Sporadic Vestibular Schwannoma: A Review

Abstract: Quality of life (QoL) measures are increasingly used as outcome measures in the assessment of different treatment options in clinical practice and as endpoints in clinical trials. Methods and questionnaires currently used for QoL assessment in vestibular schwannoma (VS) patients, studies evaluating QoL before and after treatment, studies on patients managed conservatively and studies evaluating facial-nerve-function-related QoL in VS patients are reviewed. Current methodological controversial issues in QoL stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 76 publications
0
22
0
1
Order By: Relevance
“…By default, the SF-36 has become the most widely used instrument for assessing HRQOL outcomes within the VS literature. 12 Importantly, the SF-36, GBI, and PROMIS-10 are multipurpose instruments and therefore are heavily influenced by patient comorbidity and may lack the sensitivity required to detect subtle changes after treatment or small differences between management arms. 4,9,11 In 2010 Shaffer and colleagues introduced the disease-specific PANQOL scale, a 26-item questionnaire evaluating facial function, balance, hearing, pain, anxiety, energy, and general health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By default, the SF-36 has become the most widely used instrument for assessing HRQOL outcomes within the VS literature. 12 Importantly, the SF-36, GBI, and PROMIS-10 are multipurpose instruments and therefore are heavily influenced by patient comorbidity and may lack the sensitivity required to detect subtle changes after treatment or small differences between management arms. 4,9,11 In 2010 Shaffer and colleagues introduced the disease-specific PANQOL scale, a 26-item questionnaire evaluating facial function, balance, hearing, pain, anxiety, energy, and general health.…”
Section: Discussionmentioning
confidence: 99%
“…20 Within the last 20 years there has been growing interest within the medical community to develop methods for quantifying patient-perceived outcomes, understanding there is often disparity in what we as health care providers prioritize and what patients value. 2,9,12,26 Previous attempts to ascertain which treatment strategy ultimately provides the best quality of life for patients with small-to medium-sized VSs have been severely hampered by small numbers, short follow-up, potentially important selection biases, lack of a disease-specific quality of life analysis, and no nontumor control group for comparison. 9 After an extensive review of the recent literature, Gauden and colleagues concluded that since most studies have relied on the 36-Item Short Form Health Survey (SF-36) and have reported outcomes in disparate ways, no strong conclusion can be drawn regarding the merits of one treatment over another, and the existing literature suffers significantly from monomethod biases.…”
mentioning
confidence: 99%
“…10,11 The few published prospective studies involved patients with small VSs (< 3 cm). 20,24,26 To our knowledge there is only one prospective report of QOL in patients with larger tumors (> 3 cm), and that study involved 37 patients.…”
Section: 25mentioning
confidence: 99%
“…In patients presenting with profound hearing loss, comparative prospective studies have not found any statistically significant difference among those undergoing SRS and those undergoing microsurgery in terms of quality of life. 36 Whitmore et al 111 recently reported the results of a comprehensive quantitative, statistically driven study designed to determine which treatment modality yields the best quality of life at 5-and 10-year follow-up in patients with VSs smaller than 25 mm in diameter who present with some residual hearing. Even though the study was limited by the assumptions the authors had to make to come up with the best possible comparative model, it provided useful insights into treatment-related morbidity parameters and their influence on postoperative quality of life.…”
Section: Hypothetical Casementioning
confidence: 99%